First records of the antlion genus Solter Navás from southern Africa, with description of a new species (Neuroptera: Myrmeleontidae: Myrmecaelurini) - Mansell, Mervyn W. (Zootaxa, 2013)
A new species of Solter Navás is described from South Africa, representing the first record of this genus from Africa south of the equator. This is a significant extension to the known distribution range of this predominantly Palaearctic genus. The species described here is characteristically reddish brown with a banded abdomen, and was recorded at three localities in arid rocky areas in the Northern Cape Province of South Africa.